U.S. Electrical System Reliability: Deregulated Retail Choice States' Evidence and Market Modeling - Prentis, Eric L. (International Journal of Energy Economics and Policy, 2014)
The goal of this paper is to test if the promised U.S. electrical system high reliability standards are being maintained, once states deregulate their electric utilities. This research is the first in the literature to combine states that offer retail choice, by deregulating their electric utilities, with North American Electric Reliability Corporation reserve margin forecasts, from 2014-2023, to analyze whether deregulated retail-choice states are adding adequate generating capacity to meet demand, and thus provide high electrical system reliability, when compared to the U.S. as a whole. This paper’s results on electrical system reliability in the deregulated states are timely and important for U.S. electricity energy policy. Additionally, this is the first paper in the literature to propose a new space-time business model that adequately addresses the complex, multidiscipline, multidimensional, U.S. electrical system deregulated market. Future research will specify the new business model’s mathematical formulation. Keywords: U.S. electrical system reliability; Electric utility deregulation; Electricity “energy only” and “capacity markets.” JEL Classifications: G31; G38; H44; K23